2017
DOI: 10.1007/s00405-017-4809-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum amyloid A in nasal polyps is associated with systemic corticosteroid insensitivity in patients with chronic rhinosinusitis with nasal polyps: a pilot study

Abstract: Our findings suggest that increased SAA in NP is associated with reduced response to oral corticosteroids in CRSwNP. SAA levels in NP may have potential value in predicting corticosteroid insensitivity in CRSwNP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
3
14
1
1
Order By: Relevance
“…Our previous studies reported that SAA expression is remarkably elevated in CRSwNP patients, and its level in polyp tissues has potential value in predicting systemic corticosteroid insensitivity in patients with CRSwNP. 17,25 Here, we extended our previous studies and found that the tissue SAA levels were significantly higher in both non-ECRSwNP and ECRSwNP compared to the healthy subjects. In addition, the tissue SAA levels were further elevated in the patients with disease-controlled compared to those with the disease partly controlled and uncontrolled.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies reported that SAA expression is remarkably elevated in CRSwNP patients, and its level in polyp tissues has potential value in predicting systemic corticosteroid insensitivity in patients with CRSwNP. 17,25 Here, we extended our previous studies and found that the tissue SAA levels were significantly higher in both non-ECRSwNP and ECRSwNP compared to the healthy subjects. In addition, the tissue SAA levels were further elevated in the patients with disease-controlled compared to those with the disease partly controlled and uncontrolled.…”
Section: Discussionsupporting
confidence: 81%
“…The endoscopy score for nasal polyps (NPs) was calculated for each nasal cavity by nasal endoscopy as previously described [ 21 ]. Each nasal cavity was graded as follows: 0 = no polyps; 1 = small polyps in the middle meatus not reaching below the inferior border of the middle concha; 2 = polyps reaching below the lower border of the middle turbinate; 3 = large polyps reaching the lower border of the attachment of inferior turbinate or polyps medial to the middle concha; 4 = large polyps causing almost complete congestion/obstruction of the inferior meatus.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were not used corticosteroid agents, immune suppressive agents and anti-allergy agents at least one month prior to the recruitment. To determine whether the patients were at the CR status, following established procedures 6 , patients were prescribed with oral corticosteroids (30 mg of prednisone once daily for 14 days). Polyp scores were assessed before and after the treatment with oral corticosteroids; subjects with polyp size reduced ≤ 1 score were categorized to the CR (CR) group, otherwise the CS group ( Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…CR is common in chronic airway diseases, including severe asthma, chronic obstructive pulmonary disease, nasal allergy (AR) and chronic rhinosinusitis 3 , 5 , 6 . To find hints to elucidate the pathogenesis of CR, we collected nasal epithelial cells (NECs) of patients with nasal allergy, nasal polyposis with or without CR.…”
Section: Introductionmentioning
confidence: 99%